Interaction effect of pressurized lamination pipe by using 2D finite element analysis - Norhaida, Ab. Razak; Ahmad Syahrizan, Sulaiman; Nasrul Azuan, Alang (IOP Publishing, 2012)
The availability of the multiple sites is often observed in pipeline and their interaction and coalescence may significantly affect their life. In this paper the finite element method has been used to study the effect of pressure defect on the stress field and their interaction in the interlaminar region. The effect of the crack size and the pressure defect will be investigated. The results are presented as the evolution of the stress field in the interlaminar region as a function of the pressure defect. It is observed that for two cracks with equal length, the pressure inside the lamination give greater value than those for unequal length.